Comparative Study of Technology Integration and Challenges in Higher Education: A Case Study of the UK and India - Gopinath Vedula, Venkata Subramanya (International Journal of Advances in Business and Management Research (IJABMR), 2025)
The technological advancement has made a great stride in Higer Education not only in India but across the globe. The present study has made a comparative analysis of the adoption of technology in higher education in Great Britain and India. While attempting to trace the opportunities and the possible challenges while implementing the technology at higher educational institutions, we have examined the available infrastructure, teaching staff preparedness, level of student engagement and the national government policies and regulations. The study also probes into the barriers on the way to implementing tools in learning and management systems and the resistance from execution staff. The study revealed that institutions in the United Kingdom (UK) are leaning more on technology, while the Indian institutions still face resistance in implementation. The gaps in the process of shift are common for both India and UK while the degree varies. The study also offers suggestions for an effective implementation of the technology in higher education.